But I am an alligator: charlie and lola - Child, Lauren (Puffin Books London, 2012)
In "But I Am an Alligator," the narrative explores themes of identity and self-acceptance through the eyes of an alligator navigating a world that misunderstands him. As he grapples with the expectations of his environment, the story delves into the struggle between societal norms and personal truth. Through vivid imagery and poignant moments, the alligator's journey challenges perceptions and invites readers to reflect on their own identities.